Markowitz 2.0: Innovations for asset allocation - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2012)
The idea of conducting financial analysis on asset classes, while widely accepted today, was a new concept in the 1950s. It was so new that Nobel Prize winner in economics Harry Markowitz almost did not receive his doctorate because his thesis on portfolio optimisation was deemed as “not economics” by his supervisor. Dr Paul Kaplan, quantitative research director at Morningstar, introduces an updated model of Markowitz’s portfolio optimisation model at a seminar in SMU.